The influence of environmental concern and attitudes towards sustainable consumption on beef meat purchase intention - Quevedo-Silva, Filipe; Lima-Filho, Dario de Oliveira; Freire, Otávio (Revista de Administração da UFSM, 2015)
The purpose of this paper is to analyze the influence of environmental concern and attitudes towards sustainable consumption on the purchase intention of environmentally sustainable beef meat. Therefore, we conducted a study with 300 beef consumers of Campo Grande-Mato Grosso do Sul, the capital of the second largest state of Brazil in terms of slaughter. We conducted a probability sample. We adopted the method of uniform stratified sampling. The survey was conducted with face-to-face interviews. Data were analyzed using descriptive statistics and structural equation modeling. The results indicate that environmental concern influenced sustainable beef meat purchase intention directly and indirectly. Furthermore, formal education influenced consumers’ level of environmental concern, presenting a moderating effect on the proposed model. The results also indicate that the purchase intention of consuming a meat with an attribute of environmental sustainability is still low among consumers. This paper contributes by being the first to study environmental sustainability at the beef’s Agribusiness system including the perspective of the consumer. Furthermore, we provide data that suggest that education is more relevant than income for the sustainable consumption.